Evaluation of diagnostic parameters of scales of overcontrol and low control of the questionnaire of neurotic disorders - L. I. Tsidik (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
To date, there is an urgent need to develop psychometric scales that would not depend on the distribution of assessments and on the construct itself. Creation of such scales is possible only on the basis of technologies that are not conceptually related to distribution parameters. These technologies include the Rush model. The purpose of the study: to evaluate the diagnostic parameters of the scales of overcontrol and low control of the questionnaire of neurotic disorders. Surveyed 296 people. The main statistical method of work is the Rush metric system. Results: on the basis of the metric system Rasha developed new scales: a scale of overcontrol and a scale of low control of the questionnaire of neurotic disorders; statements of both scales have adequate constructive validity; measures of difficulty points — within the regulatory range from -2 to +2 logites; both scales are one-dimensional, have a balanced metric structure; reliability index supercontrol scale is 0.78, and the low control scale — 0.76; scales are able to differentiate 3 levels of severity of properties.